Sports graduate capabilities and competencies: a comparison of graduate and employer perceptions in six EU countries. Issue 2 (3rd April 2017) - Baker, Colin; Loughren, Elizabeth A.; Dickson, Tabitha; Goudas, Marios; Crone, Diane; Kudlacek, Michal; Petr, Michal; Petrova, Lucie; Pichot, Lilian; Frery, Jean Claude; Benoit, Anne; Knobé, Sandrine; et al.
Abstract: The graduate employment market faces ever-increasing socio-economic and political pressures. Higher Education Institutions and the sport sector in the EU have an important role in contributing to graduate employment. The aims of the study were: (1) to assess general perceptions of employability, and (2) to assess sports graduates' and employers' perceptions of specific capabilities and competencies in order to identify possible improvements for sports graduate employability programmes. A cross-sectional survey of sports graduates and employers was administered in six EU countries including the UK, France, Germany, Spain, Greece and the Czech Republic to assess graduate and employer perceptions. A graduate capabilities and competencies framework was devised to assess personal, interpersonal, cognitive, role-specific and generic skills. Responses were elicited from 1132 sports graduates and 327 employers. There was generally a wide difference of opinion between employers and sports graduates in terms of the importance and possession of a number of capabilities and competencies. There is a need for the Higher Education sector and employers to take responsibility in ensuring that work experience, work placement and volunteering opportunities are embedded in curricula and to ensure the fitness of purpose of what and how graduate capabilities and competencies are assessed.